Case Study : AZ Puncak Trading / Muhamad Ayreeq Mazlan - Mazlan, Muhamad Ayreeq (2021)
The main purpose of this case study conducted because to expose students to real business through a case study. Aster taking several factors into account, I had done a basic research on the local companies I had selected and identified their company background. The name of the company that I had chosen is A Z Puncak Trading. The pioneer of this company is Mr. Ariffin bin Daud. A Z Puncak Trading is a general contracting company which created on 29 October 1996. This firm specialized in mechanical contracting, supplying, construction, preconstructions service, job site and project management and most basic contracting services. A Z Puncak trading main objective is to provide a top quality service towards all side so that customers will satisfied and perceive great value. This firm is based at Pengkalan Chepa Kota Bharu Kelantan.